Analisis perhitungan harga pokok produksi pada Catering Dapoer Laziid (Pendekatan variabel coasting) - Annisa Shalvira Siregar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the calculation of the cost of production at Catering Dapoer Laziid. Catering Dapoer Laziid is a business engaged in catering that produces types of food ranging from food to catering for large parties and events as well as catering for daily meals. Catering Dapoer Laziid serves orders in large quantities so a detailed breakdown of production costs is needed. Dapoer Laziid Catering is located in the Medan Johor area, Medan City. The data research technique in this research is descriptive with qualitative. After researching and analyzing the process of calculating the cost of production using the Variable Costing method at Catering Dapoer Laziid using the variable costing method, it can help MSMEs in calculating production costs, where this variable costing method separates production and non-production costs, namely fixed costs. and variable costs. There are several MSMEs that have not taken into account the cost of electricity and marketing costs into the cost of production, where these costs also include costs incurred even though they are not included in direct production costs in the Catering process at Dapoer Laziid. This resulted in the difference in the selling price between the calculation of Catering Dapoer Laziid and variable costing.